PEMBINAAN AKUNTANSI BERBASIS DIGITAL BAGI PESERTA DIDIK SMA KRISTOFORUS 1 JAKARTA - Emillia Sastrasasmita; Florence Delvina; Vincent King Joeliant; Eric Bryan Lie (Jurnal Serina Abdimas, 2026)
In today's digital era, traditional accounting systems are starting to be abandoned. Businesses of all sizes are adapting to the rapid development of information technology by adopting digital accounting. Digital accounting is considered to shorten the financial recording process, increase efficiency in terms of time and costs, while ensuring compliance with regulations. The process of preparing users to use accounting software is the background to the importance of accounting training at the advanced stage. The various features available in Accurate software can be useful and run effectively if supported by the accountant's ability and willingness to operate a computer. The PKM team believes that accounting software training can be carried out for high school students, because students are already accustomed to using computers and are familiar with technology. The method of implementing accounting training in this community service is (a) the organizer briefly explains the purchasing cycle in Accurate; (b) then the questions are discussed by the organizer by showing how to input each transaction in Accurate via a projector, and followed by each student on their respective laptops; (c) the organizer gives quiz questions to be done as an evaluation of understanding; and (d) the meeting ends with students filling out a questionnaire as feedback from the training activities. The outputs produced are in the form of participation in Senapenmas 2025 which is held periodically by Tarumanagara University, copyright on IPR and products. Pada era digital saat ini, sistem akuntansi tradisional mulai ditinggalkan. Bisnis dari berbagai skala melakukan penyesuaian diri atas perkembangan teknologi informasi yang cukup pesat dengan mengadopsi akuntansi digital. Akuntansi digital dinilai dapat mempersingkat proses pencatatan keuangan, meningkatkan efisiensi dari segi waktu dan biaya, sekaligus memastikan kepatuhan terhadap regulasi. Proses mempersiapkan user dalam menggunakan software akuntansi menjadi latar belakang pentingnya pembinaan akuntansi pada tahap lanjutan. Aneka fitur yang tersedia pada software Accurate dapat bermanfaat dan dijalankan secara efektif apabila didukung dengan kemampuan dan kemauan akuntan dalam mengoperasikan komputer. Tim PKM percaya bahwa pelatihan software akuntansi dapat dijalankan bagi peserta didik di SMA, karena siswa sudah terbiasa menggunakan komputer dan akrab dengan teknologi. Adapun metode pelaksanaan pembinaan akuntansi pada pengabdian ini adalah (a) penyelenggara menjelaskan secara singkat siklus pembelian yang terdapat pada Accurate; (b) kemudian soal dibahas oleh penyelenggara dengan menampilkan cara input setiap transaksi pada Accurate melalui proyektor, dan diikuti oleh setiap siswa pada laptop masing-masing; (c) penyelenggara memberikan soal quiz untuk dikerjakan sebagai evaluasi pemahaman; dan (d) pertemuan diakhiri dengan siswa mengisi kuesioner sebagai feedback dari kegiatan pelatihan. Luaran yang dihasilkan berupa keikutsertaan pada Senapenmas 2025 yang diadakan berkala oleh pihak Universitas Tarumanagara, hak cipta pada HKI dan produk.